Watch out for reporter gene assays with Renilla luciferase and paclitaxel - Theile, Dirk; Spalwisz, Adriana; Weiß, Johanna (Analytical biochemistry, 2013)
Luminescence-based reporter gene assays are widely used in biochemistry. Signals from reporter genes (e.g., firefly luminescence) are usually normalized to signals from constantly luminescing luciferases such as Renilla luciferase. This normalization step can be performed by modern luminometry devices automatically providing final results. Here we demonstrate paclitaxel to strikingly enhance Renilla luminescence, thereby potentially flawing results from reporter gene assays. In consequence, these data advocate for careful examination of raw data and militate against automatic data processing.